Modeling of interdiffusion in poly(vinyl acetate)–poly(methyl methacrylate)–toluene multicomponent systems. Issue 8 (8th October 2018) - Raupp, Sebastian M.; Kitz, Paul G.; Siebel, David K.; Wunsch, Alexander; Merklein, Lisa; Scharfer, Philip; Schabel, Wilhelm
ABSTRACT: Work on interdiffusion has been mainly carried out in binary systems in the past, and this work has focused on polymer–solvent (S) systems and polymer blends. To understand and predict the interdiffusion of two solids in the presence of one S, we present a new mathematical model based on the Onsager approach. Within our model, interdiffusion kinetics are described with a modification of the reptation model for long polymer chains, and the chemical potential gradient is used as the driving force behind mass transfer. The chemical potential is calculated with a Flory–Huggins approach. The model was validated with 29 Raman spectroscopy experiments in poly(vinyl acetate)–poly(methyl methacrylate)–toluene systems at 20 °C. Monomer mobilities ( L i, 0 s) were determined for both polymers to show the independence of L i, 0 from the chain length. The L i, 0 s were found to be strongly dependent on the S content. With the knowledge of phase equilibria and L i, 0 s, interdiffusion in the ternary polymer–polymer–S system could be predicted by the introduced model. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47092. Abstract :